DAMPAK KERJASAMA INDONESIA-AUSTRALIA: BIDANG PENDIDIKAN (STUDI KASUS SISTER SCHOOL SMPN1 TASIKMALAYA DENGAN GLENUNGA INTERNATIONAL HIGH SCHOOL AUSTRALIA) 2012 - Anggara, Billy; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This research describes educational cooperation Indonesia - australia case study:sister school SMPN1 tasikmalaya with glenunga International High School in 2012.Indonesia is a nation that has a fundamental problem in education. Then, efforts to improvethe quality of education is not negotiable in order to improve the quality of human resourcesin Indonesia. To solve the problems, Indonesia has the initiative to cooperate with the State,one of which Australia.The research method used is a descriptive of qualitative research method about thefacts. This research is an explanatory that describe about problem, indication, policies,cooperation. In writing techniques, the author’s collect and collate data through libraryresearch from several sources like books, journals, articles, websites, the media and others.The author’s also use the concept of national interest in view the case in this study.The direct impact is the increased economic value of the activity of educationalservices in both countries. Indirect impacts are from increased trading activities in bothcountries Australia is working closely with its partners in developing countries to support thedevelopment priorities of each country. Australian Government aid to Indonesian students tothe bilateral relationship between Australia and Indonesia can provide benefits in thepolitical, security, socio-cultural and economic.Keywords: Education, Problem, Country, Impact